Left Gastric Vein Direct Anastomosis as Alternative to Portal Flow Reconstruction in Liver Transplantation - Raquel Lima Sampaio, MD; Gustavo Rego Coelho, MD, PhD; Denissa Ferreira Gomes Mesquita, MD; Carlos Eduardo Lopes Soares, BM; José Huygens Parente Garcia, MD, PhD (Annals of Surgery Open)
Introduction:. The most relevant limiting factor for performing end-to-end anastomosis is portal vein thrombosis (PVT), which leads to challenging vascular reconstructions. This study aimed to analyze a single center’s experience using the left gastric vein (LGV) for portal flow reconstruction in liver transplantation (LT). Methods:. This retrospective observational study reviewed laboratory and imaging tests, a description of the surgical technique, and outpatient follow-up of patients with portal system thrombosis undergoing LT with portal flow reconstruction using the LGV. This study was conducted at a single transplant reference center in the northeast region of Brazil from January 2016 to December 2021. Results:. Between January 2016 and December 2021, 848 transplants were performed at our center. Eighty-two patients (9.7%) presented with PVT, most of whom were treated with thrombectomy. Nine patients (1.1% with PVT) had extensive thrombosis of the portal system (Yerdel III or IV), which required end-to-side anastomosis between the portal vein and the LGV without graft, and had no intraoperative complications. All patients had successful portal flow in Doppler ultrasound control evaluations. Discussion:. The goal was to reestablish physiological flow to the graft. A surgical strategy includes using the LGV graft. According to our reports, using LGV fulfilled the requirements for excellent vascular anastomosis and even allowed the dispensing of venous grafts. This is the largest case series in a single center of reconstruction of portal flow with direct anastomosis with the LGV without needing a vascular graft.